Atuação de profissionais da Psicologia nas unidades de acolhimento para pessoas em situação de rua no Sistema Único de Assistência Social (SUAS) em Cuiabá - Oliveira, Erika Aparecida de (2023)
This dissertation, developed in the Study and Research Group in Social Community Psychology (Comuni) of the Post-Graduation Program in Psychology (PPGPsi) at the Federal University of Mato Grosso (UFMT), in the city of Cuiabá, is based on the theoretical framework of Latin American community social psychology and popular education, supported by authors such as Maria de Fátima Quintal (1996), Martín Baró (1996), Paulo Freire (2019), Sílvia Lane (1996), and others. The study is configured as qualitative exploratory research, using interviews to gather data for analysis. Thus, this work aims to understand the role of psychology professionals in the Brazilian public policy of Social Assistance (named SUAS) in Cuiabá, on the state of Mato Grosso, in the level of high-complexity on the special protection, that contain adult shelter units responsible for the care and sheltering individuals experiencing homelessness. Through interviews with two psychology professionals, the study attempts to address the service demands that reach the units, relying on the conceptions of the National Social Assistance Policy regarding access to social rights through temporary care and shelter, access to healthcare, and other resources advocated in the legislations. The professionals can recognize their role within the team; however, this collective work is only realized within the social assistance unit, as outside the service, there is a tendency toward bureaucratization, isolation from other public policy teams, and lack of effectiveness in intersectoral collaboration.